O processo de requalificação profissional do Instituto Nacional de Seguridade Social (INSS) – Agência De Francisco Beltrão/PR no período de 2015 a 2018 - Marsango, Daliane Jacqueline (2020)
The work, essential to build the individual identity - besides its situations and organizations -, in detriment of unnumbered ways and innovations, it still brings some risks due to its performance. The disabling injuries, arising of repeated risks which sequels are reflected in the society, needs appropriated policies to protect the worker. In this way, vocational rehabilitation is an important public policy adopted to reintegrate the worker in the formal job market and try to get an earning to the worker and businessman, more over reliefs the public coffers from compensatory/lifetime assistance resulting from the lack of injured worker rehabilitation. This survey investigate the educational role together the professional rehabilitation process, since they- rehabilitation and education – are intrinsically connected to inherent goals of adaptation or rehabilitation process, as well, as the education or reeducation in the way to develop a new ability which provides a reentrance in the job market. The data refers to the period from 2015 to 2018 which sees the process Split and its repercussion that conducts to a discussion about the Program effectiveness. Due to resulting analysis of this period, there is an amount of 124 concluded orientations. From them, only 21% of insured people returned to the same function or a different function pursued before the accident and can effectively be considered professionally rehabilitated. It is understood this theme has a long way to be tracked, it is realized through the extension of effects, since prejudiced view of this Program individuals are submitted, the insufficient protection to the rehabilitated people; the little effectivity of schooling in the rehabilitated people life and the evident governmental intention to reduce the expenses.